Design of Ionic Liquid Crystals Forming Normal-Type Bicontinuous Cubic Phases with a 3D Continuous Ion Conductive Pathway - Takahiro Ichikawa; Yui Sasaki; Tsubasa Kobayashi; Hikaru Oshiro; Ayaka Ono; Hiroyuki Ohno (Crystals, 2019)
We have prepared a series of pyridinium-based gemini amphiphiles. They exhibit thermotropic liquid−crystalline behavior depending on their alkyl chain lengths and anion species. By adjusting the alkyl chain lengths and selecting suitable anions, we have obtained an ionic amphiphile that exhibits a normal-type bicontinuous cubic phase from 38 °C to 12 °C on cooling from an isotropic phase. In the bicontinuous cubic liquid−crystalline assembly, the pyridinium-based ionic parts align along a gyroid minimal surface forming a 3D continuous ionic domain while their ionophobic alkyl chains form 3D branched nanochannel networks. This ionic compound can form homogeneous mixtures with a lithium salt and the resultant mixtures keep the ability to form normal-type bicontinuous cubic phases. Ion conduction measurements have been performed for the mixtures on cooling. It has been revealed that the formation of the 3D branched ionophobic nanochannels does not disturb the ion conduction behavior in the ionic domain while it results in the conversion of the state of the mixtures from fluidic liquids to quasi-solids, namely highly viscous liquid crystals. Although the ionic conductivity of the mixtures is in the order of 10−7 S cm−1 at 40 °C, which is far lower than the values for practical use, the present material design has a potential to pave the way for developing advanced solid electrolytes consisting of two task-specific nanosegregated domains: One is an ionic liquid nano-domain with a 3D continuity for high ionic conductivity and the other is ionophobic nanochannel network domains for high mechanical strength.